1978
DOI: 10.1128/iai.21.2.648-654.1978
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Certain Cations (Fe, Zn, Mg, and Ca) on Bacterial Endotoxins

Abstract: The natural occurrence of cations Fe, Zn, Mg, and Ca in the lipopolysaccharide (LPS) of both the S and R forms of Shigella dysenteriae 1 was studied. LPS preparations were obtained either by phenol-water extraction (according to the method of Westphal et al., Z. Naturforsch. 7b:148-155, 1952) or by extraction of cells with hypertonic sodium chloride-sodium citrate (according to the method of Raynaud and Digeon, C. R. Acad. Sci. (Paris) 229:564-566,1949), with subsequent chromatographic purification on Sephadex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A broad screening of LPS from several sources was beyond the scope of this paper. However, it is worth noting that LPS is known to bind a number of metals (Lewis and Dixon, 1971; Šourek and Tichý, 1975; Šourek et al ., 1978), which are certain to be present in bacterial culture media. Copper contamination of LPS prepared by phenol extraction (such as the lots used in this study) has been previously reported at similar levels to those we describe here (Šourek and Tichý, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…A broad screening of LPS from several sources was beyond the scope of this paper. However, it is worth noting that LPS is known to bind a number of metals (Lewis and Dixon, 1971; Šourek and Tichý, 1975; Šourek et al ., 1978), which are certain to be present in bacterial culture media. Copper contamination of LPS prepared by phenol extraction (such as the lots used in this study) has been previously reported at similar levels to those we describe here (Šourek and Tichý, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Cations, including iron, are known to complex naturally with LPS. 21 We reasoned that iron lost from heme in destabilized hemoglobin might become associated with the LPS in the hemoglobin-LPS complexes. In fact, our most recent studies demonstrated saturable binding of iron to LPS.…”
Section: Introductionmentioning
confidence: 99%